THE ROLE OF ISLAMIC RELIGIOUS INSTRUCTORS IN THE RELIGIOUS AFFAIRS OFFICE (KUA) OF PANDAN DISTRICT, CENTRAL TAPANULI REGENCY IN NON-FORMAL EDUCATION - Suwanto; Junaidi Arsyad; Solihah Titin Sumanti (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the role   of Islamic Religious Extension Workers in the Office of Religious Affairs (KUA) of Pandan District, Central Tapanuli Regency in Non-Formal Education. Then analyze the concept of Non-Formal Education carried out by the Islamic Religious Extension Division of KUA, Pandan District, Central Tapanuli Regency and analyze  how the supporting and inhibiting factors of the Role of Islamic Religious Extension Officers in KUA, Pandan District, Central Tapanuli Regency in Non-Formal Education. The type of research is qualitative with reduction analysis, presentation and data verification techniques. The results of the study include : first; the role of Islamic religious extension workers in KUA Pandan District shows that Islamic religious extension workers play a role in fostering religion in the al-barakah taklim council. Second; The roles carried out are as educators (Muaddib) and as information straighteners (Musaddin). The concept of non-formal education carried out by the field of religious extension science KUA Pandan District, Central Tapanuli Regency, there are three methods that religious extension workers do, namely the lecture method, the story method and the educational method. Third; The supporting and inhibiting factor of the role of Islamic religious extension workers in KUA, Pandan District, Central Tapanuli Regency in non-formal education is the supporting factor with the activities of the Al-Barakah Circle taklim council getting good support and appreciation from the Kalangan Village apparatus